A Novel Strategy for the Synthesis of N-Alkylated Oxindoles - Thien, Nguyen Duc; Ngoc, Hoang Kim; Nam, Nguyen-Hai; Anh, Duong Tien; Baecker, Daniel (Synlett, 2025)
The synthesis of N-alkylated oxindoles remains an important focus in organic chemistry, due to their common occurrence in bioactive compounds and pharmaceutical agents. An efficient novel strategy for alkylating the oxindole scaffold at the N-1 position is described. By using (N-methylpyrrol-2-yl)methylidene as a protecting group for the competing C-3 position, this methodology provides a simple and mild procedure to convert various oxindoles into their corresponding N-alkylated and N-benzylated derivatives in moderate to good overall yields (up to 67%).
Keywords: oxindoles; alkylation; regiochemistry; protecting group